The Link of Abnormal Accrual Mispricing and Value- Glamour Stock Anomaly: Evidence from the Indonesian Capital Market - Erni Ekawati (Gadjah Mada International Journal of Business, 2012)
The purpose of this study is to investigate whether abnormal accrual mispricing acknowledged in accounting literature is a manifestation of documented value-glamour anomaly in finance literature. This study proposes the traditional value-glamour proxies (sales growth, book-to-market, earningprice, cash flows-price, and size) and CFO/P ratio (ratio of operating cash flows and stock price) to explain the mispricing of abnormal accruals. Using a sample of 540 firm-year observations of companies listed on the Jakarta Stock Exchange (JSE) from the period of 1993 to 2003, the study finds that individually, only either the E/P or CFO/P ratio can pick up the mispricing attributed to abnormal accruals. These results can be interpreted as follows: (1) as captured by E/P ratio, abnormal accrual mispricing is due to the market’s inability to understand managers’ attempts to manage reported earnings; (2) as captured by the CFO/P, the market is unable to assess the persistence of cash flows. From a practical standpoint, this study has simplified the research agenda related to asset pricing. The result suggests that a researcher can control for the abnormal accrual mispricing and the value-glamour anomaly parsimoniously via just one variable, E/P ratio.Keywords: business performance; entrepreneurial orientation; environmental uncertainty